2000
DOI: 10.1002/1521-3765(20001117)6:22<4154::aid-chem4154>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic Polypropionate Fragments for Detecting Stereoselective Aldolases

Abstract: A series of fluorogenic polypropionate fragments has been prepared. These undergo retroaldolization to an intermediate aldehyde that liberates the fluorescent product umbelliferone by a secondary beta-elimination reaction. leading to a >20-fold increase in fluorescence (lambda(em) = 460 +/- 20 nm, lambdaex = 360 +/- 20 nm). By applying the principle of microscopic reversibility to the reversible aldol reaction, we can use these substrates to detect stereoselective aldolases. Test substrates are available to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…S2 †) that report on TzMe-removal by a uorescence turn-on signal. 46,47 The uorogenic probes were synthesized by ether-ication of the phenolic dyes with 3-(bromomethyl)-6-(tertbutyl)-1,2,4,5-tetrazine (3), which can be accessed by bromination (PBr 3 ; 88%) of 2 (Fig. 2b).…”
Section: Isonitrile-induced Removal Of Tzme-groups From Phenolsmentioning
confidence: 99%
“…S2 †) that report on TzMe-removal by a uorescence turn-on signal. 46,47 The uorogenic probes were synthesized by ether-ication of the phenolic dyes with 3-(bromomethyl)-6-(tertbutyl)-1,2,4,5-tetrazine (3), which can be accessed by bromination (PBr 3 ; 88%) of 2 (Fig. 2b).…”
Section: Isonitrile-induced Removal Of Tzme-groups From Phenolsmentioning
confidence: 99%
“…Oxidation of the secondary alcohol to the corresponding ketone allowed subsequent β‐elimination of umbelliferone as a fluorogenic process, an assay which was also coupled to ester hydrolysis to enable the detection of enantioselective lipases 12 . The principle was exploited for aldol type substrates for aldolase catalytic antibodies (2) 13 and transaldolases (3) 14 More recently, we showed that the simple probe (4) , 15 which undergoes enolization followed by elimination of the fluorescent product umbelliferone, allows one to detect aldolase‐active small molecule and dendritic catalysts 16 . The same principle can be extended for indirect probes for lipases and acylases by releasing (4) as a reaction product 17 …”
Section: Separating the Enzyme Reactive Group From The Fluorophorementioning
confidence: 99%
“…The ADH assay above can be modifi ed in the form of aldol substrates such as 6 to assay retro -aldolization reactions via a retro -aldol/ β -elimination sequence. The aldolase substrate 6 and analogs are prepared by direct synthesis from aldehyde 4 (Scheme 1.2 ) [9,10] . Aldehyde 4 is unstable towards β -elimination in water, but can be handled in organic solvent.…”
Section: Fluorogenic Aldolase Probesmentioning
confidence: 99%
“…forward reaction lies in the possibility of testing individual stereoisomers of the aldol product for reactivity, leading to a prediction of stereoselectivity, as was analyzed using all eight diastereoisomers of aldol 6 [10] .…”
Section: Alcohol Dehydrogenases (Adhs) and Aldolasesmentioning
confidence: 99%